1998
DOI: 10.1103/physrevlett.80.1284
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure ofNiS1xSexacross the Phase Transition

Abstract: We report very highly resolved photoemission spectra of NiS1−xSex across the so-called metalinsulator transition as a function of temperature as well as composition. The present results convincingly demonstrate that the low temperature, antiferromagnetic phase is metallic, with a reduced density of states at EF . This decrease is possibly due to the opening of gaps along specific directions in the Brillouin zone caused by the antiferromagnetic ordering.While metal-insulator transition has been one of the outst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 16 publications
3
18
0
Order By: Relevance
“…For the preparation of the millerite samples, polycrystalline samples of hexagonal NiS was prepared first by solid state reaction [1,7]. Hexagonal NiS sample was then sealed in quartz tube in high vacuum and was maintained at 573 K for about 2-3 weeks and was cooled slowly to room temperature over a period of 8 hours, to obtain the millerite phase.…”
Section: Methodsmentioning
confidence: 99%
“…For the preparation of the millerite samples, polycrystalline samples of hexagonal NiS was prepared first by solid state reaction [1,7]. Hexagonal NiS sample was then sealed in quartz tube in high vacuum and was maintained at 573 K for about 2-3 weeks and was cooled slowly to room temperature over a period of 8 hours, to obtain the millerite phase.…”
Section: Methodsmentioning
confidence: 99%
“…Effects of substituting other elements for Ni or S have been also studied in detail. 7,8 Recently, two high-resolution photoemission studies 9,10 have revealed a finite density of states (DOS) around the Fermi energy (E F ) in the LT phase, but they have given contrasting interpretations: Nakamura et al 9 have concluded that there is a small correlation-induced band gap with an unusually sharp band edge, and that the observed finite DOS at E F is due to thermal and instrumental broadenings of the edge. On the other hand, Sarma et al 10 have concluded that the LT phase is an "anomalous metal".…”
mentioning
confidence: 99%
“…Many other basic physical properties of the hexagonal NiS can be found in the related Refs. [11][12][13]. As Hall coefficients could not be observed in the HT phase [8], the defects in that phase are inconclusive.…”
Section: Introductionmentioning
confidence: 85%